Geochemical processes of groundwater salinization in an arid area, southeastern Tunisia - Dhaoui, Oussama (2021)
Groundwater salinization is a major problem throughout arid and semi-arid areas due to different natural processes and anthropogenic activities and has caused irreparable environmental and economic effects. Groundwater vulnerability of Menzel Habib has been firstly assessed using multiple methods such as DRASTIC, DRASTIC pesticide, SINTACS and SI models. These indices are based on combination of intrinsic and specific characteristics of the aquifer. Almost the area presents a low to moderate vulnerability with the highest vulnerability on the western region, associated to lower deep of groundwater and evaporation processes, with consequent salinity increase. Total Dissolved solids (TDS), chloride, sodium, sulfate, calcium and magnesium water contents were determined in a total of twenty-five groundwater samples from Menzel Habib aquifer. The accuracy of the best robust model was evaluated by the correlation between the different vulnerability indices and contamination water indicators. On the Menzel Habib aquifer area, a modified vulnerability index called DRASTIC_Sal was applied including total dissolved solids water content. This index is a simple and transparent approach for salinization vulnerability assessment of aquifers, particularly inland aquifers from arid and semi-arid regions with associated agricultural activities.